Employee Training And Development On Organizational Performance Using Systematic Literature Review Analysis - Octaviani, Ririn; Musafirul syahmi; Emila Riza; I Putu Gede Wiradharma; Muhammad Fauzi; Hidayati, Tetra (Cita konsultindo, 2025)
This study aims to analyze the impact of employee training and development on organizational performance through a systematic literature review approach. By examining various relevant studies, it was found that training and development significantly influence employee performance across different industry sectors. The results indicate that well-structured and continuous training programs not only enhance employees' skills and knowledge but also contribute to their motivation and job satisfaction. Furthermore, employee development through mentoring and coaching programs has proven effective in strengthening their commitment to organizational goals. This research concludes that investment in training and development is a crucial strategy for organizations to achieve competitive advantage and improve overall productivity. The findings are expected to serve as a guide for managers in designing more effective human resource development programs.